2005
DOI: 10.1103/physrevb.72.045426
|View full text |Cite
|
Sign up to set email alerts
|

Island formation and dynamics of gold clusters on amorphous carbon films

Abstract: Samples of Au clusters deposited by laser ablation on an amorphous-carbon substrate are investigated. After a few months storage at room temperature the initially statistically distributed clusters are found to be collected in agglomerates consisting of larger clusters embedded in an Au film typically covering areas of size 25×70 nm 2 . The Au film is determined to be probably 4 to 8 monolayers but at most 7 nm thick. Evidence is found that a number of clusters consisting of less then 50 atoms are pinned at in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…This is the reason why Au and Mo can hardly form vapour droplet at experimental temperature (lower than 850°C) in TEM. From the viewpoint of diffusion, Au can diffuse in α-C film even at room temperature forming Au islands after months of storage [28], but it is apparently not as rapid as the diffusions of Cu on α-C film. It has to be pointed out however that although there is no Au nano-particle being detected in Figs.8, extremely small and rather fewer amounts of Au nano-particles may form during heating, which is beyond the detecting limit of normal microscope [29].…”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why Au and Mo can hardly form vapour droplet at experimental temperature (lower than 850°C) in TEM. From the viewpoint of diffusion, Au can diffuse in α-C film even at room temperature forming Au islands after months of storage [28], but it is apparently not as rapid as the diffusions of Cu on α-C film. It has to be pointed out however that although there is no Au nano-particle being detected in Figs.8, extremely small and rather fewer amounts of Au nano-particles may form during heating, which is beyond the detecting limit of normal microscope [29].…”
Section: Discussionmentioning
confidence: 99%
“…The interatomic forces were calculated by using a semi-empirical many-body potential proposed by Sutton and Chen 29 . For the interaction with the amorphous carbon support, a parameterized Lennard-Jones 6-12 potential obtained from ab-initio calculations 30 was applied. Initially, the cluster was thermalized at 0.4 K. Throughout the landing process, the time step was set to 5 fs and increased after 50 ps to 10 fs, during thermalization to the substrate temperature of 300 K. After 250 ps, the system is fully thermalized and finally evolved for 1 ns with a time step of 20 fs.…”
Section: Methodsmentioning
confidence: 99%
“…1b displays an island consisting of a continuous Au film (region with darker contrast compared to a-C film) with embedded Au clusters, which is formed after the sample was stored about four months at room temperature in a sealed container in air. A detailed analysis in combination with Monte-Carlo (MC) simulations revealed that the embedding Au film results most likely from diffusion and agglomeration processes of very small Au species, which stem from the cluster source operating without mass selection [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have carried out transmission electron microscopy (TEM) experiments regarding the temporal behaviour of statistically distributed Au clusters with a diameter d < 4 nm deposited on amorphous carbon (a-C) films by laser ablation [12]. Experimentally, after a four months storage at room temperature it was observed that Au clusters embedded in a thin Au film with a typical area of 25 · 70 nm 2 are formed, which modify significantly the initial statistical particle distribution found immediately after the deposition.…”
Section: Introductionmentioning
confidence: 99%